2021
DOI: 10.7759/cureus.19908
|View full text |Cite|
|
Sign up to set email alerts
|

Spontaneous Rupture of Large Angiomyolipoma of the Kidney: A Rare Case

Abstract: Angiomyolipoma is the most frequent neoplasm of the kidney. It may have a wide range of clinical manifestations, but it is usually detected incidentally on cross-sectional images. Rupture and hemorrhage of angiomyolipoma is an important concern for large lesions. We present the case of a 42-year-old female, with no history of urinary stones, who presented with a sudden-onset left flank pain for eight hours. Upon examination, she was tachycardic and hypotensive. Abdominal examination revealed a left-sided flank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…Findings on the pre-contrast CT scan were bilateral AML and a subcapsular hematoma with suspected ongoing bleeding in the right kidney. It has been reported that a common cause of spontaneous subcapsular hematoma is AML [7] which is the most typical benign solid kidney tumor. AML contains blood vessels, spindle cells, and fatty tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings on the pre-contrast CT scan were bilateral AML and a subcapsular hematoma with suspected ongoing bleeding in the right kidney. It has been reported that a common cause of spontaneous subcapsular hematoma is AML [7] which is the most typical benign solid kidney tumor. AML contains blood vessels, spindle cells, and fatty tissues.…”
Section: Discussionmentioning
confidence: 99%
“…AML is one of the most common types of kidney tumor. It consists of muscle, fat, and blood vessels, so it is prone to bleeding [7,8]. Hence, we report a unique case of a 42-yearold man who suffered from paralytic ileus as a presentation of APS and the challenging anticoagulant therapy due to ongoing bleeding renal AML.…”
Section: Introductionmentioning
confidence: 96%
“…Angiomiolipom je najčešća benigna neoplazma koja može biti uzrokom ovoga sindroma, pogotovo kada je veći od četiri centimetra. Angiomiolipom se u 80 % bolesnika javlja sporadično, dok kod ostalih 20 % bolesnika može biti povezan s mutacijama u genima TSC1 i TSC2 5 . Kod tumora koji su veći od 4 cm, postoji veća mogućnost stvaranja aneurizama unutar lezije, a time i mogućnost krvarenja što je opisano kod većine pacijenata s Wunderlichovim sindromom 6 .…”
Section: Raspravaunclassified
“…Tumor rupture, particularly in angiomyolipomas (AML) and renal cell carcinomas (RCC), is the primary cause of WS [ 6 ]. Non-tumor causes include infections, coagulation disorders, stone disease, and vascular factors, such as vasculitis, arteriovenous malformations, renal vein thrombosis, and renal aneurysms [ 7 ].…”
Section: Introductionmentioning
confidence: 99%